Endothelin‐1 contributes to the progression of renal injury in sickle cell disease via reactive oxygen species. (19th December 2015) - Brett Heimlich, J; Speed, Joshua S; O'Connor, Paul M; Pollock, Jennifer S; Townes, Tim M; Meiler, Steffen E; Kutlar, Abdullah; Pollock, David M
Abstract : Background and Purpose: Endothelin‐1 (ET‐1) is increased in patients with sickle cell disease and may contribute to the development of sickle cell nephropathy. The current study was designed to determine whether ET‐1 acting via the ETA receptor contributes to renal injury in a mouse model of sickle cell disease. Experimental Approach: Adult, humanized HbSS (homozygous for sickle Hb) mice had increased ET‐1 mRNA expression in both the cortex and the glomeruli compared with mice heterozygous for sickle and Hb A (HbAS controls). In the renal cortex, ETA receptor mRNA expression was also elevated in HbSS (sickle) mice although ETB receptor mRNA expression was unchanged. Ligand binding assays confirmed that sickle mice had increased ETA receptors in the renal vascular tissue when compared with control mice. Key Results: In response to PKC stimulation, reactive oxygen species production by isolated glomeruli from HbSS sickle mice was increased compared with that from HbSA controls, an effect that was prevented by 1 week in vivo treatment with the selective ETA antagonist, ABT‐627. Protein and nephrin excretion were both elevated in sickle mice, effects that were also significantly attenuated by ABT‐627. Finally, ETA receptor antagonism caused a significant reduction in mRNA expression of NADPH oxidase subunits, which may contribute to nephropathy in sickle cell disease. Conclusions and Implications: These data support a novel role for ET‐1 in the progression of sickle nephropathy, specifically via the ETA receptor, and suggest a potential role for ETA receptor antagonism in a treatment strategy.